Evidence of empowerment in hotel industry : the case of hotel front liners in Malaysia - Abdul Aziz, Yuhanis; Awang, Khairil Wahidin; Samdin, Zaiton (2011)
Empowerment plays a critical role in maintaining service excellence, especially when facing demanding customers in the rapidly evolving tourism industry. The purpose of this paper is to consider the concept of empowerment in the context of hotel industry. More specifically, this research has two objectives: to explore the level of empowerment practice in the Malaysian context; and to examine if demographic and other factors have an effect on empowerment. Data were collected from four major departments in four and five star hotels. The analysis of the study revealed evidence of employee empowerment practice in the Malaysian hotel industry. The results provided evidence of a high level of empowerment in the Malaysian hotel industry. Results further indicate that there was a significant difference between the four major ethnics in empowerment perceptions. Finally, the analysis shows that experience differs considerably in terms of their empowerment perceptions. This paper concludes with a discussion of the managerial and research implications.